The Frequency of Involuntary Autobiographical Memories and Future Thoughts in Relation to Daydreaming, Emotional Distress, and Age - Berntsen, Dorthe (Conscious Cogn, 2015)
We introduce a new scale, the Involuntary Autobiographical Memory Inventory (IAMI), for measuring the frequency of involuntary autobiographical memories and involuntary future thoughts. Using the scale in relation to other psychometric and demographic measures provided three important, novel findings. First, the frequency of involuntary and voluntary memories and future thoughts are similarly related to general measures of emotional distress. This challenges the idea that the involuntary mode is uniquely associated with emotional distress. Second, the frequency of involuntary autobiographical remembering does not decline with age, whereas measures of daydreaming, suppression of unwanted thoughts and dissociative experiences all do. Thus, involuntary autobiographical remembering relates differently to aging than daydreaming and other forms of spontaneous and uncontrollable thoughts. Third, unlike involuntary autobiographical remembering, the frequency of future thoughts does decrease with age. This finding underscores the need for examining past and future mental time travel in relation to aging and life span development.